Disrupting Online Racism Against Māori In Aotearoa/New Zealand - Rankine, Jennifer Margaret (AoIR Selected Papers of Internet Research, 2017)
This visual presentation will describe a study that developed anti-racist graphics in an attempt to disrupt dominant anti-Māori discourses on news Facebook pages in Aotearoa/New Zealand. The 1840 Tiriti (Treaty) o Waitangi acknowledged the sovereignty of the indigenous Māori but was ignored by colonists. This resulted in the loss of most Māori land and the ongoing marginalisation of Māori people. The study advanced a critical theory of Tiriti-based transformational change, and focused on the inconsistencies and paradoxes in dominant discourses. Reviews indicate that anti-racist interventions should also be respectful; evoke empathy or outrage; undermine dominant culture hegemony; change social norms; and provide accurate information to dispel false beliefs. Humour is the main factor contributing to online artefacts becoming widely-shared memes. The paper will illustrate the process of developing 80 sometimes humorous anti-racist graphics, and describe responses to them in comments about Māori items on news Facebook pages. It will also present an analysis of two graphics which were widely shared on participants’ personal Facebook pages, indicating the potential of online interventions to bring new digital networks to counter-hegemonic speech communities. The research resulted in a transferable four-step process for developing counter-hegemonic alternatives to dominant online discourses: 1) Identify the discourses affecting particular populations; 2) Analyse contradictions and paradoxes; 3) Develop humorous visual and text alternatives; and 4) Evaluate their online impact. This process has been adopted by Tiriti education groups in New Zealand.